Evaluating main order contract forms for Major Industrial Plant Projects (MIPP) with respect to completion and performance of design risk allocation - Anita Erbe (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2013)
Contracts should be matched to the unique situation of a Major Industrial Plant Project (MIPP). However, in reality, oftentimes contract forms are chosen that do not fit participant's (owners', contractors') competences and risk capabilities. In this paper, MIPP order contract forms are evaluated for the most common settings of owners and contractors with respect to allocation of completion and performance-of-design risks. The research method takes a qualitative approach by using grounded theory and expert interviews. 39 interviews were conducted with a total of 48 interviewees - professionals from EPC and EPCM contractors, main technical component suppliers, consultants and representatives of owners. Firstly, it is defined what a MIPP is - considering technical as well as monetary terms. Secondly, using concepts of New Institutional Economics (NIE), the international context and the MIPP network of contracts are studied. Based on Project Finance literature, the commercial risks involved in a MIPP are laid-out. Focusing on the main order contract, the involved parties are termed, introducing a "standard situation" with typical core competences of owners and contractors. Finally, using results from the expert interviews, the core MIPP order contract forms - ownermanaged, EPC, EPCM, and deviations thereof are evaluated, illustrated by examples. Appropriate contractual risk allocation depends on the specific MIPP situation - to be understood by a thorough analysis of the owner's competences, capacities and experience in relation to the project. – – Das vorliegende Arbeitspapier untersucht die im internationalen Großanlagenbau verwendeten Vertragsstrukturen für den Hauptliefervertrag (Werkvertrag). Nach einer Definition des Begriffs "Großanlagenbauprojekt" (Major Industrial Plant Project, MIPP) werden mittels der Neuen Institutionenökonomik und Projektfinanzierungs-Literatur das internationale Umfeld, die Risiken und Vertragsparteien des Werkvertrags analysiert. Unter Zuhilfenahme von Experteninterviews werden die Vertragsformen EPC, EPCM und owner-managed sowie einige Mischformen insbesondere in Bezug auf die Allokation von Fertigstellungs- und Konstruktionsrisiken evaluiert. Eine Kernkompetenz-, Kapazitäts- und Erfahrungsanalyse des Bauherrn in der Planungsphase ist die entscheidende Grundlage für die Wahl der Vertragsform.
Keywords: L14; G32; L24; L70; L74; 330; major industrial plant projects; construction; contracting out; investment; financing; contractual risk allocation; reputation; order contract forms; owner-managed; general contractor; EPC lump-sum turnkey; EPCM; EPC+; EP(CM); split EPC